-44-9x=-31-3x

Simple and best practice solution for -44-9x=-31-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -44-9x=-31-3x equation:


Simplifying
-44 + -9x = -31 + -3x

Solving
-44 + -9x = -31 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-44 + -9x + 3x = -31 + -3x + 3x

Combine like terms: -9x + 3x = -6x
-44 + -6x = -31 + -3x + 3x

Combine like terms: -3x + 3x = 0
-44 + -6x = -31 + 0
-44 + -6x = -31

Add '44' to each side of the equation.
-44 + 44 + -6x = -31 + 44

Combine like terms: -44 + 44 = 0
0 + -6x = -31 + 44
-6x = -31 + 44

Combine like terms: -31 + 44 = 13
-6x = 13

Divide each side by '-6'.
x = -2.166666667

Simplifying
x = -2.166666667

See similar equations:

| 60x=50(x+36) | | 2x(3+5)=25 | | 2x(3+5)= | | 3y-3+9=8y+6-5y | | Z^2+11z+24= | | 72x^3+32x^4-16x^5=0 | | 12b^3-9b^2=0 | | a^2-3a-40=0 | | X^3-3y^3z^2= | | a^2+2a-17=-2 | | 8x^2+22x+121=0 | | 5x=2(3+x) | | 7x=3x^2-6 | | (x)*(x^2+3)=35 | | (b+3)(b-6)=0 | | x^3+3x-35=0 | | 5x^2+11x=-2 | | 3m-35=21+14m | | 7x+12y=200 | | 4x^2=21x-5 | | 3m-35=12+4m | | 7(x-7)=126 | | -6(10-4x)=-3(-12-8x) | | -6y-14=7y+25 | | 2(2y-1)-2(2y)=2 | | x(5x-8)=13 | | 3x-9x^3= | | B=9-a | | 3x(x+1)=(2x+3)(x+1) | | -225T+T=T | | 2x^6+8x^4-6xy^2= | | T=9(5T)2 |

Equations solver categories